Structural characterization of phase transition of Al2O3 nanopowders obtained by polymeric precursor method - Cava, S.; Tebcherani, S. M.; Souza, I. A.; Pianaro, S. A.; Paskocimas, C. A.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2007)
Nanocrystalline Al(2)O(3)powders have been synthesized by the polymeric precursor method. A study of the evolution of crystalline phases of obtained powders was accomplished through X-ray diffraction, micro-Raman spectroscopy and refinement of the structures through the Rietveld method. The results obtained allow the identification of three steps on the gamma-Al2O3 to alpha-Al2O3 phase transition. The single-phase alpha-Al2O3 Powder was obtained after heat-treatment at 1050 degrees C for 2 h. A study of the morphology of the particles was accomplished through measures of crystallite size, specific surface area and transmission electronic microscopy. The particle size is closely related to gamma-Al2O3 to alpha-Al2O3 phase transition. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Al2O3; phase transition; polymeric precursor method; nanopowders; micro-Raman spectroscopy; crystallite size